Tolerance to Some ACCase Inhibitors in Four Common Roegneria (Roegneria kamoji) Populations From China - Tang, Wei; Yu, Xiaoyue; Chen, Jie; Xie, Lei; Lu, Yongliang (Frontiers in Agronomy, 2020)
Common roegneria, a perennial weed in Roegneria genera of the tribe Triticeae (family: Poaceae), is widely distributed in China and could not be effectively controlled by Acetyl coA carboxylase (ACCase) inhibitors in wheat in some regions. This study aimed to quantify herbicide tolerance level and investigate its mechanisms of ACCase tolerance in common roegneria. Whole-plant dose-response assay indicated that populations ZJJX and HBJZ (collected in wheat fields) exhibited high tolerance (ED50s>16-fold labeled field rate, LFR) to fenoxaprop-P-ethyl and clodinafop- propargyl (aryloxyphenoxypropionate, APPs), and pinoxaden (phenylpyrazolin, DEN). In addition, two populations collected from uncultivated areas, showed similar responses to these herbicides. All common roegneria populations were susceptible to haloxyfop-R-methyl and quizalofop-p-ethyl (APPs), clethodim and sethoxydim (cyclohexanedione, CHDs) (ED50s<1/2-fold LFR). The responses to ACCase inhibitors of common roegneria were in complete accord with wheat. ACCase sequencing revealed that the APPs tolerance was not conferred by known amino acid substitutions. The sensitivity of common roegneria populations to fenoxaprop-P-ethyl could not be reduced by metabolic inhibitors malathion and 4-chloro-7-nitro-benzoxadiazole. In vitro ACCase enzyme activity assays revealed that the activities of ACCase were increased in ZJJX, ZJHZ populations and wheat after fenoxaprop-P-ehtyl treatment, which at 72 h after treatment (HAT) was 1.46, 1.39 and 1.34-folds higher than that at 0 HAT, respectively. To our knowledge, this study reported for the first time the natural tolerance to ACCase inhibitors in common roegneria. The enhanced ACCase activity suggested that rapid metabolism of the herbicide might play an important role in the tolerance mechanism of this weed. Rotated with other crops (i.e. oilseed rape) to use different herbicides could serve as important tools for managing common roegneria in wheat.